The structural and magmatic evolution of the Lebombo monocline, South Africa, with particular reference to Swaziland - Cleverly, R; Cleverly, R. W. (1977)
﻿ The Lebombo Monocline is a large flexure of Karroo age extending from Southern Rhodesia to Natal. It consists mainly of a thick sequence of Karr basalts and rhyolites overlying the Archaean crust. The Karroo strata dip eastwards beneath Cretaceous cover at angles of up to 50°. Four 1:50,000 detailed maps have been produced of the volcanics in Swaziland. The basalts form a monotonous and poorly exposed succession. They are about 5 km thick but a large dyke swarm and strike-faulting serve to increase the apparent thickness. A few acidic interbeds occur near the base. The rhyolites overlie the basalts with little interbedding. They are also about 5 km thick and can be divided into 30 flows which are interpreted as rheoignimbritic in origin because of the presence of characteristic ignimbrite features and flow-folded tops to the flows. A dense dyke swarm intrudes the basalts and is younger than most of the basaltic succession; five granophyre bodies intrude the basalts close to the base of the rhyolites. The monocline is block-faulted in the south but becomes progressively more flexural in the north. The jointing in the rhyolites can be divided into groups related to basement structures, monoclinal flexuring and post-Karroo tectonic activity respectively. Major and trace element analyses for seventy rocks show that the chemical variation in the rhyolites can be explained by Rayleigh fractionation of a dacitic magma produced by fractional crystallisation of a basaltic precursor. The more basic and most acid rhyolites have compositions more compatible with partial melting of a solid basaltic source. The rhyolite magma was nearly dry but the vapour phase was rich in CO2. The acidic interbeds within the basalts have depleted trace element abundances and relatively radiogenic isotopic chemistry and were produced by crustal anatexis. The tectonics and magmatism of the Lebombo are discussed in relation to the break-up of Gondwanaland.